Lokaltherapie solitärer intrapulmonaler maligner Rundherde - Winkel, Jan op den; Eichhorn, Florian; Rieken, Stefan; Dienemann, Hendrik (Der Radiologe, 2017)
Intrapulmonary nodules generally represent an incidental finding in the roentgenogram or computed tomography (CT) scan of the chest. They are defined as single, well-circumscribed, radiographic opaque lesions that measures up to 3 cm in diameter and are surrounded completely by aerated lung. The probability of malignancy directly correlates with increasing diameter. Lesions that have a diameter of 1 cm or larger require direct evaluation.